Ethnomethodology and the study of online communities (Information Research: An International Electronic Journal, 1998)
Drawing from the authors’ current research programs, this essay explores the basic dimensions of online communities and the concomitant need for scholars to rethink the assumptions that undergrid historic paradigms about the nature of social interaction, social bonding, and empirical experience (Cerulo, 1997). In so doing, we argue that online communities are far from the “imagined” or pseudo communities explicated by Calhoun (1991); that they are, in fact, “real” in the very way in which they reflect the changing nature of human relations and human interaction. Finally this paper discusses the epistemological and methodological implications of studying cyber communities. We will discuss how computer-mediated interaction, or telelogic communication, as it has been characterized by a number of theorists (Ogan, 1993; Ball-Rokeach & Reardon, 1988), can be analyzed to contribute to phenomenological or ethnographic understandings of what it means to be a member of a cyber-community. We suggest that one of the best approaches to taking such a phenomenological snapshot is through a multi-method triangulation, employing qualitative interviews and descriptive and inferential analyses of message content. We also will address limitations and restrictions for using the Internet to do ethnomethodology.